2005
DOI: 10.4141/a04-051
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and behavioural changes in Holstein calves during and after dehorning or castration

Abstract: [131][132][133][134][135][136][137][138]. Physiological and behavioural responses of 17 bull and 12 heifer dairy calves (80.9 ± 1.4 kg) to either hot-iron dehorning or dehorning followed by scalpel castration were compared to both control and sham procedures and to each other. Blood samples were collected via jugular catheters at 15 and 30 min, 1, 2, 4, 24, and 48 h post procedure, sham or control. Cortisol levels remained elevated above controls for at least 2 h after castration and 30 min after dehorning. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 23 publications
5
13
0
Order By: Relevance
“…Our results support and extend the findings reported by Schwartzkopf-Genswein et al (2005), in which 1-to 2-mo-old Holstein bull calves were disbudded by hot iron cautery and then approximately 21 d later were surgically castrated. In that study, as in the present report, cortisol concentrations reached maximum peaks at approximately 30 min for both procedure groups, but then a more sustained response in the castrated calves resulted in significant differences between groups in cortisol concentrations at the 120 and 240 min time points, similar to what we observed in calves undergoing the DH 1 -CAST 2 sequence in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results support and extend the findings reported by Schwartzkopf-Genswein et al (2005), in which 1-to 2-mo-old Holstein bull calves were disbudded by hot iron cautery and then approximately 21 d later were surgically castrated. In that study, as in the present report, cortisol concentrations reached maximum peaks at approximately 30 min for both procedure groups, but then a more sustained response in the castrated calves resulted in significant differences between groups in cortisol concentrations at the 120 and 240 min time points, similar to what we observed in calves undergoing the DH 1 -CAST 2 sequence in our study.…”
Section: Discussionsupporting
confidence: 91%
“…One study has investigated separate castration and dehorning procedures in the same calves, but the procedures were performed in series, with castration always after dehorning, so comparisons between procedures were confounded with order of application (Schwartzkopf-Genswein et al, 2005). Another study has investigated castration, dehorning, and the concurrent procedure in parallel but not in series Sutherland et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Heinrich et al (2009) also reported similar increases in RR following disbudding of calves with a local anaesthetic. The HR response in the present study was similar to the levels reported in other studies (Schwartzkopf-Genswein et al, 2005;Stewart et al, 2008;Heinrich et al, 2009;Stewart et al, 200) and was lower than the increase found in calves disbudded without pain relief. There are no previous studies to compare the responses to ear-tagging; however, owing to the shorter duration and relatively little tissue damage, it is likely that ear-tagging is less painful than disbudding and this is supported by the greater behavioural and physiological response to disbudding than ear-tagging in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Schwartzkopf-Genswein and others reported that HR in dehorned calves was significantly higher that control animals for 120 minutes after the procedure [21]. Similarly, Grondahl-Nielsen et al (1999) observed that HR was elevated for 3.5 h in dehorned calves receiving no anesthetic or analgesic compared with calves that were only sham dehorned [29].…”
Section: Discussionmentioning
confidence: 99%